NILAI-NILAI PEMBELAJARAN MITIGASI GUNUNG MELETUS DALAM BUKU BACAAN ANAK - Khotimatul Husna; Husni Rahiem , Maila Dinia; Rachmy Diana , Raden (incrementapedia, 2021)
Abstract Natural disasters of erupting volcanoes are frequent disasters in Indonesia, to minimalize the negative impact of this erupting volcanoes needs mitigation. Children are the most vulnerable victims in this kind of disaster, so the child needs mitigation education in order to make the child ready well prepared to face the disasters. Mitigation outlined in children's reading books to make it easier for children to understand the material presented. Children's reading books circulating among the community certainly have standards in accordance with the standards set by the Regulation of the Minister of Education and Culture (PERMENDIKBUD). The purpose of this research is to find out how children's reading books look and deliver according to permendikbud standard No. 8 of 2016 Article 3 Paragraph 6 on Books Used by The Education Unit and to know the conformity of the contents of children's reading books with the standard pocketbooks of the National Disaster Management Agency (BNPB). This research method is descriptive qualitative, where researchers conduct book analysis with the guidelines of permendikbud No. 8 of 2016 Article 3 Paragraph 6 and mitigation of natural disasters erupting volcanoes in a pocket book written by BNPB, researchers also conduct interviews to six people who have criteria that have been set by the researchers. The results of this study are 1) the display and delivery of natural disaster mitigation education in the book has not attracted the attention of early childhood; 2) the book provides an overview of the atmosphere of the eruption of the volcanoes and uses an easy-to-understand parable; 3) the language used in the book is not easy for the child to understand; 4) the book describes the three disaster mitigations in the Pocket Book of Agile Response to Disasters; and 5) the book explains the importance of following the direction of the SAR team or rescue team, staying away from erupting volcanoes, and staying away from lava.